Phase I clinical trial of HC‐1119 soft capsule in Chinese healthy adult male subjects: Pharmacokinetics and safety of single‐dose proportionality and effects of food - Ma, Haiping; Xu, Weidong; Ni, Jin; Zhao, Naping; Tang, Shouyan; Li, Song; Cai, Tingting; Xiu, Jianping; Kang, Xin; Gao, Shen; Zhang, Li; Zhou, Tie (The Prostate, 2022)
Background Preclinical studies showed that HC‐1119, a deuterated version of enzalutamide, could competitively inhibit androgen binding to androgen receptor by blocking the transmission of androgen receptor signaling pathway as enzalutamide, inducing apoptosis of prostate cancer cells and reducing the proliferation of prostate cancer cells. Animal pharmacokinetic studies also show that deuterization of enzalutamide as HC‐1119 could retain the basic properties of mother drug, increases the stability of compounds to metabolic enzymes and the drug exposure in vivo, prolong the half‐life and reduce the production of metabolites, which may lead to a better efficacy and safety of HC‐1119 compared with enzalutamide. Methods To evaluate the pharmacokinetics and safety of HC‐1119 and the effects of food on pharmacokinetics in healthy adult Chinese men after single‐dose administration of HC‐1119. A total of 47 Chinese healthy adult male subjects received HC‐1119 soft capsule at a single oral dose of 40, 80, or 160 mg followed on fasting or 160 mg after high‐fat meal respectively. HC‐1119 prototype and its metabolites M1 and M2 in plasma were collected individually in a total 23 time points. Pharmacokinetics were determined by sensitive LC/MS/MS for dose‐proportionality study. Results In subjects taking HC‐1119 soft capsules on fasting, Cmax of HC‐1119 prototype increased dose‐dependently. Either Cmax and AUC0‐∞ of M1 or Cmax of M2 showed statistically significant difference. Dose‐proportionality evaluation showed linear pharmacokinetic characteristics in Cmax of HC‐1119 prototype, Cmax and AUC0‐∞ of M2 in dose range of 40–160 mg. Cmax of HC‐1119 was significantly different between the two groups as 160 mg HC‐1119 on fasting or after a high‐fat diet respectively, while the other parameter were not. HC‐1119 and its metabolites M1 and M2 showed a linear dynamic trend. Conclusions HC‐1119 is expected to have lower clinical dose than the similar drug enzalutamide. The absorption of HC‐1119 and the main pharmacokinetic parameters of HC‐1119 and its metabolites M1 and M2 were not affected by high‐fat diet. The clinical application of HC‐1119 soft capsule in the later stage can be recommended for both fasting and postprandial. The safety and tolerance were good in this population.